The Effect of Service Quality and Promotion on Customer Satisfaction in the Blibli.Com Application - Alfarobi, Muhammad; Aminah, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of technology and information in the world, especially the internet, is experiencing very rapid development. The internet connects one person to another, provides information, as a means of entertainment, and as a means of communication. This makes the internet a basic need for most people besides the need for food and shelter. One of the growing e-commerce developments in Indonesia today is Blibli.com. With competitive factors and complaints of dissatisfaction with the use of e-commerce in particular, Blibli.com has to increase the value they have in order to minimize users switching to other e-commerce and maintain customer satisfaction. This research aims to analyze customer satisfaction by looking at the influence of service quality and promotions on whether they can influence customer satisfaction at Blibli.com. The population in this study were people who shopped on the Blibli.com application. The sampling technique used was purposive sampling. The questionnaire method is a method for collecting data in this research. The data analysis technique for this research uses Partial Least Square (PLS). The research results show that service quality and promotion have a significant effect on customer satisfaction.